Moisture Stress and Different Rates of Nutrients on Growth and Yield of Rice - Halder, KP; Islam, MS; Manir, MR; Ali, MA (Bangladesh Rice Journal, 2019)
The experiment was conducted at the Bangladesh Rice Research Institute (BRRI) Gazipur farm during Boro 2003-04 seasons to observe the moisture stress effects in relation to nutrient rates on growth and yield of rice. The treatments were three moisture stresses (NS= Always saturated condition i.e. 1-2 cm standing water; VPS= Withholding water at the vegetative phase i.e. 15 days after transplanting (DAT) to maximum tillering stage; RPS=Withholding water at the reproductive phase i.e. PI to flowering stage) and three fertilizer doses (F0= No fertilizer; HD= Half of the optimum dose and OD= Optimum dose i.e. 120-60-40-10-2 kg ha-1 of N, P2O5, K2O, S and Zn respectively). The treatments were applied in high yielding variety BRRI dhan29. The result showed that irrespective of nutrient rates, drought stress decreased plant height, tiller number and shoot dry weight. Unstressed plants (NS) produced the highest grain yield (3.14 to 6.51 tha-1) followed by vegetative phase stressed (VPS) plants (2.73 to 4.50 tha-1). The reproductive phase stressed (RPS) plants produced the lowest grain yield (2.54 to 4.20 t ha-1). Regardless of water stress, application of optimum dose (OD) of nutrients produced the highest grain yield followed by half dose (HD) of nutrients. No fertilizer treatment (F0) produced the lowest grain yield. Due to water stress, the highest grain yield reduction occurred in OD (22-32%) followed by HD (12-19%) and the lowest in F0 (4-15%). Bangladesh Rice j. 2018, 22(2): 23-30